Results from the United States cohort of the HORIZON trial of a Schlemm canal microstent to reduce intraocular pressure in primary open‐angle glaucoma. Issue 9 (September 2019) - Jones, Jason; Koch, Douglas D.; Vold, Steven; McCabe, Cathleen; Rhee, Douglas; Lewis, Richard; Smith, Stephen; Nguyen, Quang H.; Samuelson, Thomas W.
Abstract : Purpose : To assess the safety and effectiveness of Schlemm canal stenting for reducing intraocular pressure (IOP) in combination with cataract surgery in the United States cohort of the HORIZON study. Setting : Twenty‐six clinical sites in the U.S. Design : Prospective clinical trial. Methods : Eyes with mild to moderate primary open‐angle glaucoma (POAG) on 1 to 4 medications, significant cataract, and an unmedicated diurnal IOP between 22 mm Hg and 34 mm Hg after medication washout were randomized 2:1 to receive the Hydrus microstent or no further treatment after successful cataract surgery. Patients were followed for 24 months. Medication washout and diurnal IOP measurements were repeated at 12 months and 24 months. Results : Two hundred nineteen eyes were randomized to microstent implantation and 112 patients to phacoemulsification only. At 24 months, the diurnal IOP was reduced by 20.0% or more in a greater proportion of eyes in the microstent group (78.5% versus 54.5%; P < .001). The mean change in the number of medications was −1.2 ± 0.9 (SD) in the microstent group and −0.8 ± 1.1 in the phaco‐only group ( P < .001), and 78.5% of eyes and 39.2% of eyes, respectively, were medication free (difference 38.8%; P < .001). Conclusions : Implantation of a Schlemm canal microstent after phacoemulsification significantly reduced diurnal IOP and medication use compared with phacoemulsification only in patients with mild to moderately severe POAG. The combination procedure was equivalent to cataract surgery alone in terms of visual acuity outcomes and the rate of adverse ocular events.